2012
DOI: 10.1016/j.atmosenv.2011.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Community Multiscale Air Quality (CMAQ) model performance over the North American and European domains

Abstract: Copyright 2011 Elsevier B.V., All rights reserved.The CMAQ modeling system has been used to simulate the air quality for North America and Europe for the entire year of 2006 as part of the Air Quality Model Evaluation International Initiative (AQMEII). The operational model performance of tropospheric ozone (O), fine particulate matter (PM) and total particulate matter (PM) for the two continents has been assessed. The model underestimates daytime (8am-8pm LST) O mixing ratios by 13% in the winter for North Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 19 publications
9
101
0
Order By: Relevance
“…7). Several factors contribute to the underestimation of PM 2.5 in the western US, including a lack of windblown dust and fire smoke emissions, and an underestimation of SOA formation (Carlton et al, 2010;Foley et al, 2010;Appel et al, 2012;Luo et al, 2011). Another important factor that influenced the underestimation of PM 2.5 is the overprediction of precipitation as shown in Fig.…”
Section: Evaluation Of Model Performancementioning
confidence: 99%
“…7). Several factors contribute to the underestimation of PM 2.5 in the western US, including a lack of windblown dust and fire smoke emissions, and an underestimation of SOA formation (Carlton et al, 2010;Foley et al, 2010;Appel et al, 2012;Luo et al, 2011). Another important factor that influenced the underestimation of PM 2.5 is the overprediction of precipitation as shown in Fig.…”
Section: Evaluation Of Model Performancementioning
confidence: 99%
“…Also, Pirovano et al (2012) reported a strong underestimation of ozone concentrations during the first part of the year for CAMx and CHIMERE models. CMAQ results, described in Appel et al (2012), indicate that model performance for the daytime ozone varied seasonally. In the winter, CMAQ overestimated ozone concentration by 8 % and in the spring and summer ozone levels were underestimated on average by ∼ 4 and 2 % respectively.…”
Section: Ozonementioning
confidence: 99%
“…In southern and eastern Europe, model results were underestimated. Appel et al (2012) reported that in winter the domain-averaged MBE is −21.5 µg m −3 for the CMAQ model. For other seasons the underestimation is lower -in the range of −11/ − 16 µg m −3 .…”
Section: Pm 10mentioning
confidence: 99%
See 2 more Smart Citations